Analisa Kekerasan dan Struktur Mikro Sambungan Las Kampuh V Tunggal dan Kampuh V Ganda Pada Baja Karbon Rendah - Jusman, Jusman; Sudarsono, Sudarsono; Sudia, Budiman (Teknik Mesin Universitas Halu Oleo, 2020)
The development of production technology and metal raw materials cannot be separated from the use of welding technology. So that it can be said that there is almost no metal that cannot be welded. Welding is a metal joining technique by partially melting the main metal and filler metal. The purpose of this study was to determine the hardness and microstructure of single v seam weld joint and double v seam welded on low carbon steel. In this study, using hardness testing methods and conducting microstructure observations to determine the structure formed in the welding results. The results showed that the micro structure of the single seam v was dominated by pearlite which had high hardness properties with an average value of hardness in the weld metal area of 142.80 kg / mm2, the HAZ area of 132.72 kg / mm2, and the area Main metal (Base Metal) is 121.46 kg / mm2, while the double seam v is dominated by ferrite which has low hardness properties with an average value of weld metal (Weld Metal) of 125.80 kg / mm2, HAZ area of 121 , 20 kg / mm2, and the base metal area of 112.60 kg / mm2. Keywords : SMAW, Low Carbon, hem, hardness.